Problems of urban transport in India : proceedings of the international seminar held on April 20-22, 1985 - Panduranga Rao, D. (Desari), 1948-; International Seminar on "Problems of Urban Transport in India" (1985 : Vishakhapatnam, India) (New Delhi, India : Inter-India Publications, 1986)
Proceedings of the International Seminar on "Problems of Urban Transport in India", Vishakhapatnam, 1985.
Includes index.
Bibliography: p. [365]-370.
Keywords: Urban transportation -- India -- Congresses; Urban transportation policy -- India -- Congresses